User interfaces of tomorrow, today: are mobile devices the needed impetus? - Maniega-Legarda, David (Anuario ThinkEPI, 2010)
Review of new technologies based on touch screens, voice and gestures for user interfaces. Several models and prototypes are described. The importance of usability (size, weight, design), performance, and price for the success of a new application or device is considered.